Theoretical Analysis of the Position of Kurdish media Landscape within Media Systems - Hazhan Khalid Ahmed; Salam Nasraldin Mohammed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
This study examines the media system in the Kurdistan Region of Iraq. Its objective is to identify the main categories of media systems worldwide and evaluate the Kurdish media environment in relation to these categories. The study takes a theoretical approach to investigate this topic. The key finding of the research reveals that the Kurdish media closely aligns with the polarized pluralist model. This is observed through the decline of print newspapers’ circulation and, the strong connection between politics and media, the lack of professional standards and journalistic independence, the absence of a strong national media, and the high levels of government interference in media affairs.